Eat, sleep and feel better - the impact of intermittent fasting on sleep and general well-being - Chudzik, Patrycja; Zdych, Martyna; Cisowska, Zuzanna; Bodziony, Maksym; Terebus, Andrzej; Sobala, Julia; Gaweł-Dąbrowska, Dagmara (Journal of Education, Health and Sport, 2026)
Background Intermittent fasting (IF) is a dietary pattern based on alternating fasting and feeding periods. It is gaining attention for its potential effects on sleep, health, and well-being. Current evidence on these links remains limited and inconsistent. Objective To analyze and synthesize existing studies on intermittent fasting and evaluate its potential impact on sleep outcomes and overall well-being, including possible underlying mechanisms. Methods A systematic literature search was conducted using PubMed and Google Scholar. Articles published between 2015 and 2025 were reviewed. Keywords included: circadian rhythm, intermittent fasting, sleep, quality of life. Results Intermittent fasting shows small but noticeable improvements in perceived well-being, including better mood, reduced inflammation, and enhanced cognitive functioning. Its effects on sleep remain modest and inconsistent: some studies report slight improvements in subjective sleep quality, while objective measures reveal minimal or no change, with occasional worsening of sleep efficiency. In terms of health, IF supports metabolic regulation by improving insulin sensitivity, glucose control, and lipid profile. Conclusions Intermittent fasting appears to exert variable effects on sleep and well-being and also supports metabolic health and weight control. Current research is not yet sufficient to define clear clinical guidance. IF may benefit some individuals, although its safety and effectiveness vary. More long-term, well-designed studies are needed to identify protocols that provide meaningful benefits with minimal risk.